Organizational Ambiente: Management and Environment in Chile - Wright, Richard W. (Academy of Management Journal, 1971)
The article reports on the difficulties associated with the application of industrial management processes in foreign countries. The author focuses on how executives can utilize management practices formulated in the U.S. while working in Chile. It is suggested that business enterprises that operate using management practices developed in the U.S. can be more successful in foreign economies than their local counterparts. Ways in which socioeconomic and environmental factors affect industrial efficiency and organizational effectiveness are discussed. Chilean labor laws and price regulation laws are also mentioned.